Polymorphism of apolipoprotein E gene and atherosclerosis - M. I. Voevoda; E. V. Schakhtschneider; V. N. Maximov; I. V. Kulikov; A. G. Romaschenko (Атеросклероз, 2008)
Polymorphism genes assay is of importance for estimation of predisposition to multifactorial diseases on population and individual level. We investigated apolipoprotein E polymorphism and its influence on a lipid metabolism in population of Novosibirsk city (the largest scientific and industrial centre of West Siberia). Polymorphism of apolipoprotein E (APOE) gene was studied in sample of inhabitants of Novosibirsk city aged 25‐64 years (n=611), in patients with nonfatal myocardial infarction (n=141), in patients with nonfatal stroke (n=167), in men with sudden cardiac death (n=250) and in long‐livers of the same region (n=97). A lipid profile depending on APOE genotypes was analyzed in a population and in a group of long‐livers of Novosibirsk. In male population 25‐64 years of age dynamics (changes) of frequencies APOE genotypes are not revealed. In comparison with frequencies of APOE genotypes in men is more senior than 83 years has appeared, that the frequency of a genotype ε3/ε4 has decreased 4 times, and the frequency of a genotype ε2/ε3 has increased 2 times. Among the persons of senile age and long‐livers, both men, and women the carriers of a genotype ε4/ε4 on APOE gene are not revealed. The highest level of total cholesterol in population of Novosibirsk is characteristic for a genotype APOE ε4/ε4. The introduction of genotyping of human apolipoprotein E in a population of Novosibirsk is expedient.